A Halal Cryptocurrency Model Under the Maqashid Al-Shari’ah Scheme - Mohammad Farid Fad; Ali Imron (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Innovations in economic activities are developing rapidly in this digital era. One of such innovations is the emergence of cryptocurrencies as new products in digital transactions. Cryptocurrencies can be used in the form of commodities or currencies. However, some cases related to cryptocurrencies have occurred in several countries. Given this fact, it is considered necessary to have a halal cryptocurrency formulation within the maqashid al-shari’ah frame. The analysis used in the research of a halal cryptocurrency model under the maqashid al-shari’ah scheme is descriptive-analytical in nature and complies with the ushuliyyah approach. In this model, a guarantor and a supervisor from the side of the Government are essential to eliminating the potential for chaos to occur. This model pays attention to ethical compliance with maqashid al-shari’ah which also has the principles of al-tabarruat. This application of maqashid al-shari’ah will be able to provide a framework for a cryptocurrency model that is in accordance with Islamic law. This model will also generate benefits and create quality economic growth.